2018
DOI: 10.1186/s12939-018-0860-7
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for mental health related ambulatory care sensitive conditions: what are the trends for First Nations in British Columbia?

Abstract: BackgroundIndigenous peoples globally experience a disproportionate burden of mental illness due to forced policies and practices of colonization and cultural disruption. The objective of this study was to provide a baseline profile of hospitalization rates for mental health-related Ambulatory Care Sensitive Conditions among First-Nations living both on and off reserve in British Columbia, Canada, and explore the relationship between local access to health services and mental health-related hospitalization rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Fourth, though data related to the reasons for referral and the severity of illnesses are essential for assessing the association between admissions for ACSCs and PX, we could not gather this information. Moreover, although a premature mortality rate and length of stay in a hospital are more relevant outcomes for patients,22 54 55 we could not collect the information on them due to lack of the data in the primary care clinic-based database. As a next step, an assessment of the severity/appropriateness of referrals, a premature mortality rate and length of stay may be required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, though data related to the reasons for referral and the severity of illnesses are essential for assessing the association between admissions for ACSCs and PX, we could not gather this information. Moreover, although a premature mortality rate and length of stay in a hospital are more relevant outcomes for patients,22 54 55 we could not collect the information on them due to lack of the data in the primary care clinic-based database. As a next step, an assessment of the severity/appropriateness of referrals, a premature mortality rate and length of stay may be required.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of primary care is also a problem in rural areas,17 and many studies have revealed higher rates of admissions for ACSCs in rural areas than in urban areas 10 18–21. One of the reasons could be that patients tend to be admitted at low threshold to compensate lower access to healthcare in comparison with that in urban areas 22 23. However, whether other domains of PX such as coordination, comprehensiveness or community orientation can affect admissions for ACSCs to remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While the causal direction of mental illness and diabetes is not clear, there is growing recognition that depression and other mood and anxiety disorders are a complication of diabetes [2,8]. Hospitalizations for diabetes and many of its chronic physical and mental comorbidities are considered ambulatory care sensitive, that is, potentially avoidable through appropriate management in primary care and by acting on the key underlying patient factors, such as socioeconomic status, that may place individuals at greater risk of hospitalization [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalization for ACSC is a very well recognized tool to measure access to PHC services (3,(12)(13)(14)(15)(16). Several studies have reported that higher rates of ACSC indicate barriers to PHC services (3,(17)(18)(19). We have previously used these indicators to identify gaps in the delivery of PHC in previous studies, and provided recommendations to policy makers to transform the healthcare system within these communities (3,17,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that higher rates of ACSC indicate barriers to PHC services (3,(17)(18)(19). We have previously used these indicators to identify gaps in the delivery of PHC in previous studies, and provided recommendations to policy makers to transform the healthcare system within these communities (3,17,20,21). We acknowledge that hospitalizations are linked to diagnoses and referrals: rates of hospitalization may decline as a result of barriers to PHC resulting in undiagnosed conditions and potentially premature mortality; or rates may decline as a result of early diagnosis and effective management in PHC.…”
Section: Introductionmentioning
confidence: 99%